INFLUÊNCIA DA FLEXÃO TERMOELÁSTICA NA MEDIDA DA DIFUSIVIDADE TÉRMICA DE AMOSTRAS DE ALUMÍNIO - Somer, Aloisi (2012)
The techniques they use photothermal effect, particularty the photoacoustic phenomenon, has been widely used for characterization of materials. The photoacoustic phenomenon arrises when a periodically modulate light falls on a material that absorbs radiation and produces such a variation of pressure in the gas layer adjacent to it. One technique that uses this phenomenon is the technique open photoacoustic cell (OPC), which allows obtaining the thermal diffusivity of a material, defined as= k/. The main mechanism of generation of the photoacosutic signal in solids samples is the thermal diffusion, and its mathematical model proposed by Rosencwaig and Gersho (RG model). But it is observed that the photoacoustic signal, the OPC technique, greatly influenced the thermoelastic bending mechanism which had its model proposed by Rousset et al. To characterize the photoacoustic cell, used for measurements of OPC, aluminum is used. It is used to have a high thermal diffusivity characterizing the process of thermal diffusion which has a simpler model for interpretation. In this paper we mean to obtain the thermal diffusivity of aluminum. For this we use a set of samples of aluminum cut from a same billet. In a sample, after the OPC measurements, there was a heat treatment at 300C for 48 hours to remove possible defects caused by mechanical treatments of cutting and polishing. Through model simulations of RG, we note that the dependence of the photoacoustic signal must always increase with increase frequency. This effect is not observed experimentally. The OPC measurements before and after heat treatment did not show significant differences, confirming that the treatments did not change the mechanical properties of the samples. Samples of aluminum decrease its inclination in a certain frequency range and increased again at high frequencies suggesting an influence of thermoleastic bending of the sample. The results obtained for thermal diffusivity after adjusting the experimental curves with the equation describing the photacoustic signal with contributions from diffusion and thermoelastic bending were satisfactory. Obtained values between 7,6 10 m² /and 8,8 10 m² / , and that the thermal diffusivity calculated from the definition 8,6 10 m² / s . The dependence on the thickness of the sample to a constant weight that provides the thermoelastic bending can be calculated, we find 2,82 s l and the expected value of being3 s l . So we see that the thermoelastic bending is present in the generation of the photoacoustic signal, can not be used simplifications of the RG model for the thermal diffusivity.